2008
DOI: 10.1002/art.23836
|View full text |Cite
|
Sign up to set email alerts
|

Ability of epistatic interactions of cytokine single‐nucleotide polymorphisms to predict susceptibility to disease subsets in systemic sclerosis patients

Abstract: Objective. Gene-gene interaction, or epistasis, is considered a ubiquitous component of complex human diseases such as systemic sclerosis (SSc). Epistasis is difficult to model by traditional parametric approaches; therefore, nonparametric computational algorithms, such as multifactor dimensionality reduction (MDR), have been developed. Methods. A total of 242 consecutive unrelated Italian SSc patients and an equal number of well-matched healthy controls were genotyped for 22 cytokine single-nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
2
17
0
3
Order By: Relevance
“…Specifically, haplotypes appear to be more informative in differentiating groups of interest, seem to result in a higher power of differentiation, and are less vulnerable to the adjustments of P-values because they require fewer comparisons. These findings underscore the importance of considering variation across a whole gene rather than at a particular polymorphism closely aligned with findings from medical genetics [Beretta et al, 2008;Francis et al, 2008].…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, haplotypes appear to be more informative in differentiating groups of interest, seem to result in a higher power of differentiation, and are less vulnerable to the adjustments of P-values because they require fewer comparisons. These findings underscore the importance of considering variation across a whole gene rather than at a particular polymorphism closely aligned with findings from medical genetics [Beretta et al, 2008;Francis et al, 2008].…”
Section: Discussionsupporting
confidence: 69%
“…A significant epistatic interaction between IL-2 (330T/G) and systemic sclerosis has recently been reported [20]. Our data revealed significantly increased frequencies of the G allele and the GG genotype.…”
Section: Discussionsupporting
confidence: 48%
“…In reality, in multifactorial diseases like HCV infection, where the host, the pathogen and the environmental factors all contribute to disease outcome, genetic association studies focused on a single polymorphism are often weak and non-informative. Therefore, studying the joint contribution of multiple loci that interact in the same biological pathway, such as inflammation, fibrogenesis, angiogenesis, etc., seems to be more significant in predicting disease risk by enhancing the major effects of a single gene [39,40,54,55]. In this regard, Ahluwalia et al [56] reported a tenfold increased risk of nephropathy conferred by the co-occurrence of risk-associated genotypes of three inflammatory genes, CCL2, CCR5, and MMP9 in type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory results could be partly explained by the extreme complexity in the cytokine network related to the intricate interactions of cytokines by which they induce or suppress their own synthesis or that of other cytokines, and antagonize or synergize with each other in many different and often redundant ways. On the other hand, it is now obvious that interactions between host genetic polymorphisms should be taken into account in defining complex and multifactorial disease risk, such as hepatitis C. Although the risk attributed to an individual polymorphism is often very small, it has been repeatedly demonstrated that a combination of specific genotypes may be a more significant and powerful approach in predicting disease risk [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%